Sistem Informasi Pemesanan Tiket Bus Menggunakan Algoritma Collaborative Filtering Berbasis Website - Novtra Refiardiansyah Nasution; Aninda Muliani Harahap; Adnan Buyung Nasution (Applied Information Technology and Computer Science (AICOMS), 2026)
This study aims to design and develop a web-based bus ticket reservation information system that implements a Collaborative Filtering algorithm in a smart seat booking feature. The system was developed to address the limitations of manual ticket reservation processes, including restricted access to information, long queues, and low service efficiency. The research employed the Research and Development (R&D) method using the Waterfall model, which consisted of observation, interviews, literature review, system design, implementation, and testing. System evaluation was conducted through Unit Testing, System Testing, and User Acceptance Testing (UAT). The results indicate that the system successfully provides real-time departure schedule information, facilitates online ticket reservations, and generates seat recommendations based on user preferences. All major system functions achieved a 100% success rate during testing. UAT involving 30 respondents produced a user satisfaction score of 91%, while the Collaborative Filtering algorithm achieved a seat recommendation accuracy of 85%. The system also reduced ticket booking queue times by up to 70% compared with the previous manual process..